Understanding the implementation, utilization, and potential impact of a social franchise model to improve infant and young child feeding practices in Vietnam: A program impact pathway analysis - Nguyen, Phuong Hong; Menon, Purnima; Keithly, Sarah C.; Hajeebhoy, Nemat; Mai, Lan Tran; Ruel, Marie T.; Rawat, Rahul (Wiley, 2014)
Program impact pathway (PIP) analysis helps to lay out and study the causal links between program activities, outcomes and impacts. This PIP analysis‐based study examines the pathways by which the Alive & Thrive (A&T) social franchise model is expected to improve infant and young child feeding (IYCF) practices in Vietnam. Mixed methods (surveys, observations, facility assessments) were used to assess the following elements of the PIP: 1) training and knowledge of frontline health workers (FHWs) (n =447); 2) quality of service delivery and communication with clients (n =166); 3) mothers’ service utilization (n = 2,045); and 4) the program’s role in shaping maternal behavioral determinants of IYCF practices. A&T training was associated with improved FHWs’ IYCF knowledge and counseling skills, resulting in higher quality IYCF counseling. Franchise utilization increased from 10% in 2012 to 45% in 2013, but utilization fell far below the expected 9‐15 contacts specified in A&T guidelines. Improvements in breastfeeding knowledge, intentions, and beliefs were greater among mothers in intervention areas with social franchise and mass media, compared to media alone. In conclusion, many aspects of the franchise services are encouraging, but challenges in service delivery and utilization along the PIP should be addressed to achieve the full intended impact.Grant Funding Source: Funded by Bill & Melinda Gates Foundation, through Alive & Thrive, managed by FHI360